Synthesis of Novel N,N-disubstituted Maleamic Esters and Their Applications as Plasticizers for Poly vinylchloride (Journal of the College of Basic Education, 2023)
Three N,N-Substituted Bis maleamic acids were prepared in high yields (91-94)% from reaction of maleic anhydride with o-phenylenediamine , ethylenediamine and thiourea.The corresponding Esters were prepared in high yields (85-92)% from reaction of the prepared N,N-Substituted bis maleamic acids with methanol and isopropanol. The prepared esters were tested as plasticizers for poly(vinyl chloride) and comparison the results with (DOP) and (DBP) the universal plasticizers for PVC indicated that the prepared esters in general had high plasticization efficiency.